Yellow mealworm, Tenebrio molitor (Col: Tenebrionidae), larvae powder as dietary protein sources for broiler chickens: Effects on growth performance, carcass traits, selected intestinal microbiota and blood parameters. Issue 1 (19th August 2020) - Sedgh‐Gooya, Shadi; Torki, Mehran; Darbemamieh, Maryam; Khamisabadi, Hassan; Karimi Torshizi, Mohammad Amir; Abdolmohamadi, Alireza
Abstract: This study was conducted to evaluate the effects of dietary Tenebrio molitor larvae meal (TM meal) inclusion on the performance, carcass traits, caecum microbiota and blood parameters of broiler chickens. A total of 180‐day‐old chickens were allocated to three dietary groups with five replicate pens (12 birds/pen). Experimental diets were included a corn‐soybean basal diet, and two diets with 2.5% and 5% TM. TM‐included diets have been administered for periods of starter (1–10 days) and grower (11–25 days). A regular finisher diet was given to all groups during the 26–42 days of age. Diets containing TM meal did not influence feed intake and mortality percentage. Feed conversion ratio was lower with the 2.5% TM meal diet compared with the control group at starter period ( p < .05). Besides, broiler chickens fed TM meal included diet had a higher body weight gain than the control group during 1–10 days of age ( p < .05). The carcass characteristics and length and weight of different parts of small and large intestines were not influenced by diets. TM meal inclusion decreased the albumin‐to‐globulin ratio compared with the control group ( p < .05). Additionally, lower total count of aerobic and Escherichia coli bacteria was observed in response to diet inclusion of 5% TM meal. Overall, the inclusion of TM meal in broilers' diet improved body weight gain and feed conversion ratio in the starting period, decreased albumin‐to‐globulin ratio and E. coli bacteria content.